Proceedings of SPE Annual Technical Conference and Exhibition 2006
DOI: 10.2523/102669-ms
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Stimulation of Gas/Condensate Reservoirs

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractSignificant productivity loss occurs in gas-condensate wells when the bottom hole flowing pressure drops below the dewpoint pressure. The decline in productivity is due to nearwell accumulation of condensate in the reservoir rock, which is significant even for wells producing very lean gas with liquid dropout values less than 1%. Many different methods such as hydraulic fracturing, dry gas injection and solvent injection have been proposed and implemented to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…This method can provide a long‐term solution to treat damage caused by liquid accumulation. Wettability alterations using fluoro‐components have been studied extensively in the past two decades 2–7…”
Section: Introductionmentioning
confidence: 99%
“…This method can provide a long‐term solution to treat damage caused by liquid accumulation. Wettability alterations using fluoro‐components have been studied extensively in the past two decades 2–7…”
Section: Introductionmentioning
confidence: 99%
“…Ayyalasomayajula, SPE, and J. Kamath, SPE, Chevron Firoozabadi 33 measured a strong reversal of wetting for gas and water at 284 °F, but the treatment was less successful for gas and oil. Kumar et al 4,20 evaluated several fluorosurfactants at reservoir conditions and found significant improvement in gas and condensate relative permeabilities after chemical treatment in both Berea and reservoir sandstones. The steady state gas and condensate relative permeabilities at 145 °F, 250 °F and 275 °F using different synthetic gas-condensate fluids increased by a factor on the order of 2.…”
Section: Spe 102669mentioning
confidence: 99%
“…Figure 1 shows a schematic diagram of the core flood apparatus. 4,20 The apparatus is rated for temperatures up to 400 °F and pressures up to 10,000 psig. The maximum flow rate that can be attained is in the range of 7,000 cc/hr.…”
Section: Spe 102669mentioning
confidence: 99%
See 1 more Smart Citation
“…Well deliverability reduction due to condensate blockage has been reported for some fields to reach 40 to 80% under pseudo steady-state flow of gas and condensate (Mott et al, 1999). Experimentally, more than 95% reductions in flow rates from high and low permeability rocks have been reported (Du et al, 2000;Al-Anazi et al, 2002;Kumar et al, 2006). To create and optimise reservoir development plan, including recovery strategies and productivity prediction, it is necessary to both understand and model the complex flow and phase change behaviour that occurs in gas-condensate reservoirs.…”
Section: Introductionmentioning
confidence: 99%